KUALITAS PAPAN PARTIKEL BERDASARKAN KOMPOSISI SEKAM PADI DAN KAYU SENGON DENGAN VARIASI KADAR PEREKAT - Prayoga, Dendi; Dirhamsyah, .; Nurhaida, . (Universitas Tanjungpura, 2019)
This research aimed to examine the physical and mechanical properties of particle boards based on the composition of raw materials and adhesive content and know the treatment of the composition of raw materials and the best adhesive content and meet the standard JIS A 5908-2003. The research was conducted at Wood Workshop Laboratory, Wood Processing Laboratory Faculty of Forestry,Tanjungpura University and Laboratory of PT. Duta Pertiwi Nusantara Pontianak. The adhesive used is Urea Formaldehyde with 52% Solid Content. Comparison of the composition of rice husks and sengon varies namely rice husk 50%: sengon 50%, rice husk 60%: sengon 40% and rice husk 70%: sengon 30% and variations in the levels of UF adhesives, namely 14% and 16%, with target density 0,7 gr/cm3. The particleboard was 30 cm x 30 cm x 1 cm Pressing at temperature 140oC for 8 minutes, with pressure of 25 kg/cm2. The research results of the study of density and moisture content meet the standards JIS A 5908-2003. The best particle values of rice husk and sengon with composition a ratio of rice husk 50%: sengon 50% , 16% adhesive content 16%, with density value of 0,7072 gr/cm3, moisture content 9,1949 %, thick development 12,3210 %, water absorption 68,8270 %, MOE 12110,7273 kg/cm2, MOR 161,0025 kg/cm2, firmness sticky 1,9320 kg/cm2, screw holding strength 62,3124 kg.Keywords : adhesive, composition, particle board, rice husk, sengon